FILOSOFI PENGAKUAN DAN PENGHORMATAN NEGARA TERHAdAP MASYARAKAT HUKUM ADAT dI INdONESIA - Sulastriyono .Sulastriyono (Yustisia, 2014)
Research on recognition and respect by the state to adat law community in this research as a library research. This research aims to find out and analyze about: (1) the philosophical reason of State of the Republic of Indonesia acknowledging and respecting adat law community; (2) a form of Indonesian state recognition and respect to adat law community in a variety of sectoral legislation; and (3) thinking model of recognition and honor of the Republic of Indonesia to the adat law community in Indonesia.Data collecting in this study include searches of various materials library by reading and critizising the legislations, books, journals, researchs, thesis, magazines, t are closely related to the research problem. Data from the result of library research be analysized through the process of simplification of the data so that it was easily read and interpreted.Research and discussion showed that the philosophical reasons for recognition of the Republic of Indonesia to recognize and respect the adat law community, namely Indonesian country with adat law community has a very close relationship and cannot be separated. Adat law community already exists before Indonesia’s independence. After Indonesia’s independence, adat law community is inseparable with the unitary State of the Republic of Indonesia. Adat law community is an absolute requirement of a country so that the State must recognize and honor the existence of adat law community in accordance with the goals of the State and the values of Pancasila (second Sila, third, fourth, and fifth Sila Pancasila) is stated in the preamble of Indonesia constitution of 1945. Form of State recognition and respect to adat law community in a variety of sectoral legislation there is respect for and recognition using model not by statements from adat law community but with the statement expressly by the State through a strictly layered and restrictions. In its development model recognition and observance remains with statements from countries with restrictions but loosely. Ideally, recognition and honor model by the state to the adat law community in Indonesia is by the Country Statement and loosely on the adat law community is already through the endorsement of the District or Province Gouvernment. The another model of State recognition and respect to adat law community be done carefully through the process of research and verification involving Adat law community, Government and academia.